Jenis-Jenis Anura di Deleng Ketaruman, Desa Bukum, Kecamatan Sibolangit, Kabupaten Deli Serdang Provinsi Sumatera Utara - Tri Juniati Br Ginting; Emmy Harso Kardhinata; Hanifah Mutia Z.N Amrul (Universitas Medan Area, 2020)
Research on Types of Anura in Deleng Ketaruman, Bukum Village, Subdistrict Sibolangit, Deli Serdang Regency, North Sumatera Province was conducted in February 2018. This study aims to obtain and document the types of Anura, and environmental parameters found Anura in Deleng Ketaruman, Bukum Village, Subdistrict Sibolangit, Deli Serdang Regency, North Sumatera Utara Province. The method used in this research is Visual Encounter Survey. The equipment used in this research were headlamp, background black, battery, camera, temperature and temperature gauge, plastic, frog capture net, amphibious identification book. Observation of the types of Anura was done during night. Anuras were observed only along the tracking path. The results showed that 9 species consisted of 6 families found along the tracking tracks one species of Bufonidae family (Phrynoidis juxtaspera), three species of Dicroglossidae family (Fejervarya cancrivora, F. limnocharis, Limnonectes blythii), one species of Megophrydae family (Megophrys paralella), one species of Microhylidae family (Microhyla superciliaris), two species Ranidae family (Hylarana chalconota, H. erythraea), and one species of Rhacophoridae family (Polypedates leucomystax). The ambient temperature of the Anura species ranges from 22ºC-24ºC to grassland habitats, puddles, litter and ponds.